Visual perception and motor function of children with birth-weights under 1250grams and their full term normal birth weight peers at five to six years of age : a Cape Town study - Coetzer, Dorothea (Department of Paediatrics and Child Health, 2018)
This study aimed to assess and compare the visual perceptual, visual motor integration and motor abilities of infants weighing less than 1250 grams at birth and a matched group of normal full birth weight controls at the age of five to six years. The group of infants with birth weights below 1250 grams were born during the period July 1988 to June 1989 at Groote Schuur Hospital (GSH), Cape Town or in midwife obstetric units in the Peninsula Maternal and Neonatal Service (PMNS) and referred to the neonatal intensive care unit at GSH. The very low birth weight (VLBW) infants were assessed at 1 and 2 years of age in 1989 & 1990. The present study was part of a broader study that included the examination of developmental outcome of these infants, using the Griffith's Mental Development Scale (Griffith's). The study recognised the complex interaction of biological and environmental factors and their influence on development and attempted to describe the confounds that may have influenced outcomes. The VLBW children were shorter in stature than their full birth weight counterparts. They were also significantly lighter and had smaller head circumferences. Psychometric evaluation with the Griffith's showed the VLBW children to fall predominantly in the normal range, though their performances were significantly inferior to that of the full-term children. The greatest differences between the groups were in scores for the subscales performance and practical reasoning of the Griffith's. Visual perception, visual motor integration, fine motor skill and gross motor function were all significantly poorer in the VLBW children. There was no correlation within the VLBW group between the test results and birth weight, gestational age, growth status, neonatal hospital stay or social status.